Semisolid Compression Brazing of Al50Si Alloy Using Zn-Al-Cu Filler Metal Assisted by SiC Particles - Jing Xiao; Shun Li; Shuxin Bai; Degan Xiong; Yu Tang (Advances in Materials Science and Engineering)
Semisolid compression brazing of Al50Si alloy using Zn-Al-Cu filler metal assisted by SiC particles coating has been developed. The effects of the size and concentration of SiC particles on the microstructure and mechanical properties of the joints were studied. By using 1 μm SiC particles and the concentration of SiC particles increased to 3 g/m2, oxide film on the surface of base metal was completely disrupted and a good bonding strength was obtained. As SiC concentration further increased to 4 g/m2, colonies of SiC particle with nonwetting areas of filler metal formed at the interface, resulting in a decrease in the bonding strength. By using 5 μm SiC particles, the bonding strength was enhanced as SiC concentration increased from 1 g/m2 to 3 g/m2 due to the removal of the oxide film. By further increasing SiC concentration to 16 g/m2, the strength was constantly improved because of the dislocation strengthening effect generated at the SiC particle layer/filler metal interface. When SiC concentration increased to 32 g/m2, nonwetting area appeared inside the SiC particles layer, causing a decrease in the bonding strength.